Exploring Neo-Nusantara concept in Kota Bharu, Kelantan Malaysia - Farkhan, Wan Mohamad; Abu Bakar, Nor Azlina; Zairul, Mohd (Human Resources Management Academic Research Society (HRMARS), 2024)
This study explores the integration and acceptance of Neo-Nusantara design within the architectural and urban planning practices of Kota Bharu, Kelantan, Malaysia. By employing qualitative methods such as in-depth interviews and field observations, the research examines how the community perceives and embraces traditional Nusantara elements alongside the city's Islamic identity. Key findings emphasize the importance of community involvement, cultural diversity, and religious tolerance in shaping the city's architectural identity. The study advocates for a balance between traditional and contemporary design, highlighting the need for policies that preserve cultural heritage while promoting urban growth. Challenges such as low tourism quality, poor public space maintenance, and connectivity issues are addressed with strategies like improved zoning and enhanced public awareness. The research concludes that integrating Neo-Nusantara principles can create a culturally vibrant and sustainable urban environment in Kota Bharu.